complete book of insults, boasts, and riddles - Roylance, William H. frey50 (Parker Publishing Company, Inc. West Nayack, NY, 1970)
Insults, boast, and riddles for all occations.
Insults - Boasts - Riddles - Answers to riddles
Keywords: Riddles -- Humor; Boast -- Humor; Insults -- Humor